Pendekatan klasik dan kontemporer untuk metodologi penafsiran al Quran - Fayyahd, Muh (Maliki Interdisciplinary Journal, 2024)
This article discusses the methodology of interpreting the Qur’an by combining classical and contemporary approaches. The interpretation of the Qur’an is an important scientific discipline in understanding divine messages comprehensively. The classical approach, which includes the tafsir bi al-ma’thur (based on history) and tafsir bi al-ra’yi (based on ijtihad) methods, provides a basic foundation for scholars in interpreting the verses of the Qur’an. Meanwhile, contemporary approaches introduce more contextual and critical methodologies, including hermeneutic, feminist and historical approaches. This article explores the integration between the two approaches, highlighting their strengths and weaknesses, as well as their relevance in addressing modern-day challenges. By combining classical and contemporary methods, it is hoped that the interpretation of the Koran can be more dynamic and applicable, while remaining loyal to the basic values of Islam.